Ultrasonographic evaluation of geniohyoid muscle and hyoid bone during swallowing in young adults. (5th March 2015) - Feng, Xin; Cartwright, Michael S.; Walker, Francis O.; Bargoil, Jessica H.; Hu, Yunping; Butler, Susan G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The geniohyoid muscle plays an important role in hyoid bone movement. Adequate hyoid bone movement during swallowing is important for effective bolus flow and pharyngeal clearing. The aim of this study was to estimate the relationship between the geniohyoid muscle size and function and hyoid bone movement during swallowing in healthy young adults, as measured via ultrasound, in different body positions. Study Design Cross‐sectional study. Methods Forty young (20–40 years old) adults (20 male and 20 female) participated. The cross‐sectional area of the geniohyoid muscle at rest (seated position), the geniohyoid muscle contraction velocity, and the hyoid bone displacement during swallowing 10 mL of mineral water were measured by ultrasound in seated, supine, and right lateral decubitus positions. Results The size of the geniohyoid muscle correlated with body height. Males had larger geniohyoid cross‐sectional area than females and greater maximal and anterior hyoid displacement during swallowing than females, and maximal and anterior hyoid bone displacement during swallowing correlated with the size of geniohyoid muscle only when the body was in the supine position; these two movements were positively correlated to each other. Conclusions Genders vary in hyoid bone movement during swallowing, and the correlation between geniohyoid muscle size and hyoid bone displacement varies among different body positions during swallowing. This investigation also illuminates the use of ultrasound in providing quantitative measures of geniohyoid muscle and hyoid bone displacement during swallowing. Level of Evidence 2c. Laryngoscope, 125:1886–1891, 2015